Socialization Problems in Orphans and Children Without Parental Care - Merkul I.A; Volchanskaya V.O (Moscow State University of Psychology and Education, 2022)
The process of social adaptation in graduates of orphan organizations occurs simultaneously with their socialization: as adolescents become involved in various life situations, they acquire new repertoires of social behavior or employ the ones they already have. Special attention should be paid to the specifics of development in adolescents brought up in socially deprived conditions since they tend to demonstrate asocial motivation, communicative deficits and try to avoid performing social roles. The article focuses on the problematic issues of socialization of orphans and children without parental care. To explore life situations typical for the period of independent living of graduates of orphan organizations, we used a special methodological tool: cases of life scenarios. We carried out the analysis of 452 cases of life scenarios in graduates aged 18-23 years, 262 male and 190 female. The analysis revealed the following problems of socialization and social adaptation of orphans and graduates of organizations for orphans and foster families: insufficient level of knowledge in matters of education, vocational education and employment, low goal-setting skills. We highlight the facts that are prototypical in the description of a life scenario, and these events are at the same time typical for graduates of various forms of foster care and orphan organizations.